Relationship between cardio-ankle vascular index value and stroke in hypertension patients cardio-ankle vascular index ≧9 - Jinbo Liu; Shantong Jiang; Xuechen Cui; Xiu Bai; Huan Wen; Hongwei Zhao; Hongyu Wang (PLoS ONE, 2025)
Backgrounds The cardio-ankle vascular index (CAVI) is a new index of arteriosclerosis. The present study investigated the relationship between CAVI value and stroke in hypertension patients, especially the prevalence of stroke in patients with CAVI ≧9. Methods 735 patients (M/F 293/442) with or without hypertension from Department of Vascular Medicine from 01/01/2012–31/21/2014 were divided into four groups: group 1: non-hypertension patients with CAVI<9, group 2: non-hypertension patients with CAVI ≧9, group 3: hypertension patients with CAVI<9, group 4: hypertension patients with CAVI ≧9. CAVI was measured by VS-1000 apparatus. Results Prevalence of stroke and coronary artery disease were significantly higher in group 2 than in group 1. And the prevalence of stroke and coronary artery disease were also significantly higher in group 4 than in group 3. In addition, the level of right intima-media thickness (RIMT) was significantly higher in group 4 than in group 3 (0.102±0.025 vs 0.094±0.023, p<0.05). Multiple linear regressions showed that CAVI and age were independent associating factors of stroke in all patients (β=0.268, p=0.040; β=0.135, p<0.001; respectively). CAVI was an independent associating factors of stroke in hypertension patients (β=0.398, p<0.001). Conclusion The prevalence of stroke was higher in hypertension patients with CAVI ≧9 than in hypertension patients with CAVI<9, with higher level of right intima-media thickness. CAVI was an independent associating factors of stroke in hypertension patients.